Impact of an Interactive Anti-Speeding Threat Appeal: How Much Threat Is Too Much? - Panić, Katarina; Cauberghe, Verolien; De Pelsmacker, Patrick (CyberPsychology, Behavior & Social Networking, 2011)
This study investigates the impact of an interactive television public-service announcement (PSA) containing an anti-speeding threat appeal on feelings of telepresence and behavioral intention. In a 2 × 2 × 2 between-subjects factorial design with 213 participants, the level of threat evoked by a traditional PSA, by the interactive part of the PSA (dedicated advertising location or DAL) and by the preceding program context are manipulated to be either low or high. The results support the assumptions of the Extended Parallel Processing Model with regard to the effect of the level of perceived threat and perceived efficacy in an interactive media environment, and the important role of telepresence as a processing variable. The results of the three-way interaction effect of threat evoked by the program, the PSA and the DAL on telepresence show that when the threat levels of the program and the PSA are both either low or high, exposure to the threatening information in the DAL does not generate a significantly higher feeling of telepresence. However, when a low-threat program is followed by a high-threat PSA, the threat level of the DAL has a positive effect on telepresence. The same trend is found with a high-threat program and a low-threat PSA, although the effect of the threat evoked by the DAL on telepresence is not significant at conventional levels. Finally, there is a positive effect of telepresence on the behavioral intention to reduce speeding, which is partly mediated by the viewer's perceived efficacy to follow the recommended behavior.